Preparation and gas separation properties of Zeolitic imidazolate frameworks-8 (ZIF-8) membranes supported on silicon nitride ceramic hollow fibers. Issue 7 (15th May 2016) - Wang, Jun-Wei; Li, Neng-Xu; Li, Ze-Rui; Wang, Jun-Ru; Xu, Xin; Chen, Chu-Sheng
Abstract: Zeolitic imidazolate frameworks (ZIFs) have attracted great attention due to their potential applications in gas adsorption, catalytic membrane reactors, chemical sensing and gas separation. To achieve the massive industrial application, a number of attempts have been made to prepare supported-ZIF membranes. We successfully synthesized a well-intergrown continuous ZIF-8 membrane on the outer surface of silicon nitride hollow fibers by a one-step hydrothermal method. Through controlling ZIF-8 nucleation and growth rates, the membranes were compact and well-coated. Single gas permeation of H2, N2 and CO2 at 25 °C, 0.25 MPa indicated the sieving behavior of the obtained membranes. N2 permeance did not change with permeation time, while H2 permeance increased in the beginning and keep steady at 8.35×10 −7 mol/m 2 Pa s due to the high storage properties of ZIF-8, and CO2 permeance decreased in the first hour, then maintained at 1.15×10 −7 mol/m 2 Pa s due to the strong CO2 adsorption in the ZIF-8 and the cooperative interactions of adsorbed CO2 molecules with CO2 passing through. The H2 /CO2 separation factor of 11.67 could be achieved in the separation of 50%H2 /50%CO2 mixture.